WEBVTT
00:00:01.040 --> 00:00:09.720
In this lesson, weβll learn how to find the derivative of trigonometric functions, focusing on the cotangent, secant, and cosecant functions.
00:00:10.080 --> 00:00:21.010
Weβll begin by recapping the rules that we need to find these derivatives before completing the differentiation and then considering how these standard results can help us to find the derivatives of more complex functions.
00:00:21.770 --> 00:00:27.870
Letβs begin by recapping the derivative of the trigonometric functions sine, cosine, and tangent.
00:00:28.160 --> 00:00:31.810
The derivative of sin of ππ₯ is π cos of ππ₯.
00:00:31.990 --> 00:00:35.550
The derivative of cos ππ₯ is negative π sin ππ₯.
00:00:35.640 --> 00:00:39.890
And the derivative of tan ππ₯ is π sec squared ππ₯.
00:00:40.170 --> 00:00:42.350
Weβre also going to need to use the product rule.
00:00:42.550 --> 00:00:53.460
And this is if we have two differentiable functions, π’ and π£, the derivative of their product, π’ times π£, is π’ times dπ£ by dπ₯ plus π£ times dπ’ by dπ₯.
00:00:53.710 --> 00:00:55.710
Similarly, weβll use the quotient rule.
00:00:55.890 --> 00:01:07.890
And this time, we find the derivative of the quotient of two differentiable functions, π’ and π£, by finding π£ times dπ’ by dπ₯ minus π’ times dπ£ by dπ₯ all over π£ squared.
00:01:08.220 --> 00:01:10.840
Weβll be referring to each of these throughout the video.
00:01:11.180 --> 00:01:12.920
So letβs look at first example.
00:01:13.980 --> 00:01:21.730
If π¦ is equal to negative two sec of two π₯, determine the rate of change of π¦ when π₯ is equal to 11π over six.
00:01:22.200 --> 00:01:27.630
Remember, when finding the rate of change of something, weβre actually interested in the derivative.
00:01:27.890 --> 00:01:36.590
Weβre therefore going to find the derivative of π¦ with respect to π₯ and evaluate it at the point when π₯ is equal to 11π by six.
00:01:36.870 --> 00:01:39.060
So how do we differentiate this function?
00:01:39.550 --> 00:01:43.230
Well, we begin by using the definition of the secant function.
00:01:43.410 --> 00:01:46.840
We know sec π₯ is equal to one over cos π₯.
00:01:47.110 --> 00:01:53.560
And we can write π¦ as being equal to negative two over cos of two π₯.
00:01:53.820 --> 00:01:55.740
And then, there are a couple of things we could do.
00:01:55.870 --> 00:02:02.770
We could rewrite this as negative two times cos two π₯ to the power of negative one and apply the chain rule.
00:02:03.200 --> 00:02:06.460
Or since this is written as a fraction, we can apply the quotient rule.
00:02:06.820 --> 00:02:16.720
Remember, this says that if π’ and π£ are differentiable functions, the derivative of that quotient is π£ times dπ’ by dπ₯ minus π’ times dπ£ by dπ₯ all over π£ squared.
00:02:17.110 --> 00:02:19.400
The numerator of our fraction is negative two.
00:02:19.400 --> 00:02:21.170
So we let π’ be equal to negative two.
00:02:21.340 --> 00:02:24.200
And thus π£ is equal to cos of two π₯.
00:02:24.490 --> 00:02:28.190
To use the quotient rule, weβre going to need to find the derivative of each of these.
00:02:28.550 --> 00:02:30.730
The derivative of a constant is zero.
00:02:30.790 --> 00:02:32.780
So dπ’ by dπ₯ is equal to zero.
00:02:33.340 --> 00:02:37.810
And then, we quote a standard result for the derivative of cos of ππ₯.
00:02:37.930 --> 00:02:43.050
And we see that dπ£ by dπ₯ is equal to negative two times sin two π₯.
00:02:43.280 --> 00:02:46.720
We can substitute everything we know into the formula for the quotient rule.
00:02:46.940 --> 00:02:57.570
And we see that dπ¦ by dπ₯ is equal to cos of two π₯ times zero minus negative two times negative two sin of two π₯ all over cos two π₯ squared.
00:02:57.910 --> 00:03:03.290
This simplifies to negative four sin of two π₯ over cos squared two π₯.
00:03:03.540 --> 00:03:11.020
Now, we can separate this slightly and write it as negative four sin two π₯ over cos two π₯ times one over cos two π₯.
00:03:11.250 --> 00:03:15.220
And we recall the identity sin π₯ over cos π₯ equals tan π₯.
00:03:15.460 --> 00:03:19.210
And we find we have the general result for the derivative of the secant function.
00:03:19.660 --> 00:03:25.030
Remember though, we were looking to find the rate of change of π¦ when π₯ is equal to 11π by six.
00:03:25.210 --> 00:03:30.750
So in fact, weβre going to substitute π₯ is equal to 11π by six into our expression for the derivative.
00:03:30.970 --> 00:03:34.000
And weβre actually better off leaving it here in terms of sine and cosine.
00:03:34.620 --> 00:03:37.090
We substitute π₯ is equal to 11π by six.
00:03:37.190 --> 00:03:45.960
And we get negative four sin of two times 11π by six over cos squared of two times 11π by six, which is eight root three.
00:03:46.640 --> 00:03:50.790
The rate of change of π¦ when π₯ is equal to 11π by six is eight root three.
00:03:51.910 --> 00:03:54.770
And this example has demonstrated a general result.
00:03:54.910 --> 00:04:01.350
We find that the derivative of sec ππ₯ is equal to π sec of ππ₯ times tan of ππ₯.
00:04:02.470 --> 00:04:06.800
Weβre now going to perform a similar process to help us find the derivative of the cotangent function.
00:04:07.970 --> 00:04:15.500
Determine dπ¦ by dπ₯ given that π¦ is equal to negative three cos of four π₯ plus three cot of four π₯.
00:04:15.990 --> 00:04:24.790
To find the derivative of π¦ with respect to π₯, we can individually differentiate negative three cos of four π₯ and three cot of four π₯.
00:04:25.000 --> 00:04:30.400
We know that the derivative of cos of ππ₯ is negative π sin of ππ₯.
00:04:30.650 --> 00:04:41.390
So we see that the derivative of negative three cos of four π₯ is negative three times negative four sin of four π₯, which is simply 12 sin four π₯.
00:04:41.670 --> 00:04:44.790
But what about the derivative of three cot of four π₯.
00:04:45.170 --> 00:04:49.080
Well, cot of π₯ is the same as one over tan π₯.
00:04:49.390 --> 00:04:52.950
And tan π₯ is equal to sin π₯ over cos of π₯.
00:04:53.220 --> 00:05:01.950
We can therefore say that cot of four π₯ would be the same as one over tan of four π₯ or one over sin of four π₯ over cos of four π₯.
00:05:02.310 --> 00:05:13.530
And we obtain that three cot of four π₯ is therefore three over sin of four π₯ over cos of four π₯, which can of course be written as three cos of four π₯ over sin of four π₯.
00:05:13.890 --> 00:05:19.160
So really, we need to differentiate three cos of four π₯ over sin of four π₯ with respect to π₯.
00:05:19.320 --> 00:05:21.890
And weβre going to use the quotient rule to differentiate this.
00:05:22.210 --> 00:05:25.040
We let π’ be equal to three cos of four π₯.
00:05:25.040 --> 00:05:27.000
And π£ is equal to sin of four π₯.
00:05:27.250 --> 00:05:32.690
We know that the derivative of cos of four π₯ is negative four sin of four π₯.
00:05:32.820 --> 00:05:36.370
So dπ’ by dπ₯ is negative 12 sin of four π₯.
00:05:36.670 --> 00:05:40.480
We can also use the general result for the derivative of the sine function.
00:05:40.480 --> 00:05:44.100
And we get dπ£ by dπ₯ to be equal to four cos of four π₯.
00:05:44.450 --> 00:05:48.650
We can now substitute everything we know about our function into the derivative.
00:05:48.870 --> 00:05:59.020
And we end up with sin of four π₯ times negative 12 sin of four π₯ minus three cos of four π₯ times four cos of four π₯ over sin squared four π₯.
00:05:59.470 --> 00:06:06.340
This simplifies to negative 12 sin squared of four π₯ minus 12 cos squared of four π₯ over sin squared four π₯.
00:06:06.660 --> 00:06:15.700
But if we factor negative 12, we see that the numerator of this fraction is the same as negative 12 times sin squared four π₯ plus cos squared four π₯.
00:06:15.900 --> 00:06:26.810
And we can therefore use the identity cos squared π₯ plus sin squared π₯ equals one to find that the derivative of three cot of four π₯ is negative 12 over sin squared of four π₯.
00:06:27.160 --> 00:06:29.390
Thereβs one more identity we can use.
00:06:29.470 --> 00:06:32.910
We know that one over sin π₯ is equal to cosec of π₯.
00:06:33.120 --> 00:06:43.340
And we can write negative 12 over sin squared of four π₯ as negative 12 cosec squared of four π₯. dπ¦ by dπ₯ is the sum of these two results.
00:06:43.340 --> 00:06:48.870
So itβs equal to 12 sin of four π₯ minus 12 cosec squared of four π₯.
00:06:49.990 --> 00:06:53.420
In this example, we demonstrated a result that could be generalized.
00:06:53.610 --> 00:07:00.420
We saw that the derivative of three cot of four π₯ was negative 12 cosec squared of four π₯.
00:07:00.700 --> 00:07:05.940
In the same way, we can generalize the result for the derivative of cot ππ₯.
00:07:06.080 --> 00:07:09.290
Itβs negative π cosec squared of ππ₯.
00:07:10.230 --> 00:07:20.320
In our next example, weβll look at how to find the derivative of the cosecant function, before considering how our generalised results can help us find the derivatives of more complicated functions.
00:07:21.780 --> 00:07:28.830
Given that π¦ is equal to negative 13 cosec of π plus five π₯, find dπ¦ by dπ₯.
00:07:29.290 --> 00:07:33.800
To find the derivative of the cosecant function, weβll begin by recalling its definition.
00:07:34.400 --> 00:07:38.260
We know that cosec of π₯ is equal to one over sin of π₯.
00:07:38.470 --> 00:07:42.620
This means there are a number of ways that we can find the derivative of our π¦.
00:07:43.090 --> 00:07:45.940
We could use the trigonometric sum identity.
00:07:46.450 --> 00:07:55.610
We could differentiate cosec of five π₯ and then consider the transformation that maps cosec of five π₯ onto negative 13 cosec of π plus five π₯.
00:07:56.130 --> 00:07:58.600
Or alternatively, we could use the chain rule.
00:07:58.890 --> 00:08:09.520
This says that if π¦ is a function in π’ and π’ itself is a function in π₯, then the derivative of π¦ with respect to π₯ is equal to dπ¦ by dπ’ times dπ’ by dπ₯.
00:08:09.840 --> 00:08:18.510
Weβll let π¦ be equal to negative 13 over sin π’ then, where π’ is equal to π plus five π₯. dπ’ by dπ₯ is simply five.
00:08:18.510 --> 00:08:21.930
But weβre going to need to use the quotient rule to find dπ¦ by dπ’.
00:08:22.470 --> 00:08:24.940
Weβre differentiating π¦ with respect to π’.
00:08:25.330 --> 00:08:30.270
So Iβm going to redefine the quotient rule using functions π and π in terms of π’.
00:08:30.740 --> 00:08:41.250
And we see that the derivative of π over π with respect to π’ is equal to π times dπ by dπ’ minus π times dπ by dπ’ over π squared.
00:08:41.640 --> 00:08:46.370
This means, in our case, we let π be equal to negative 13 and π be equal to sin π’.
00:08:46.750 --> 00:08:50.080
The derivative of π with respect to π’ is just zero.
00:08:50.600 --> 00:08:54.620
And we know the derivative of sin π’ with respect to π’ is cos π’.
00:08:55.030 --> 00:09:06.660
So the derivative of π¦ with respect to π’ is sin π’ times zero minus negative 13 times cos π’ over sin squared π’, which simplifies to 13 cos π’ over sin squared π’.
00:09:07.310 --> 00:09:12.260
Iβm going to write this as 13 cos π’ over sin π’ times one over sin π’.
00:09:12.720 --> 00:09:18.300
And this means dπ¦ by dπ’ can be alternatively written as 13 cot π’ cosec π’.
00:09:18.920 --> 00:09:22.650
Letβs substitute everything we have into the formula for the chain rule.
00:09:23.450 --> 00:09:29.800
Thatβs 13 cot π’ cosec π’ times five or 65 cot π’ cosec π’.
00:09:30.260 --> 00:09:33.450
We replace π’ with π plus five π₯.
00:09:33.760 --> 00:09:41.410
And we obtain dπ¦ by dπ₯ to be equal to 65 cot of π plus five π₯ times cosec of π plus five π₯.
00:09:43.260 --> 00:09:53.090
The examples weβve looked at so far give us the following results for the derivatives of the reciprocal trigonometric functions cotangent, secant, and cosecant.
00:09:53.480 --> 00:09:55.370
Itβs useful to commit these to memory.
00:09:55.640 --> 00:10:00.480
But also be aware of and ready to apply their derivation where necessary.
00:10:00.840 --> 00:10:05.850
Weβll now look at how these results can help us to find the derivative of more complicated functions.
00:10:06.420 --> 00:10:12.650
Given π¦ is equal to π₯ plus three times nine π₯ plus cosec π₯, find dπ¦ by dπ₯.
00:10:12.910 --> 00:10:16.170
Here, we have an expression which is the product of two functions.
00:10:16.330 --> 00:10:19.890
Weβre therefore going to use the product rule to calculate dπ¦ by dπ₯.
00:10:20.160 --> 00:10:28.270
This says that the derivative of the product of two differentiable functions π’ and π£ is π’ times dπ£ by dπ₯ plus π£ times dπ’ by dπ₯.
00:10:28.440 --> 00:10:34.260
We therefore let π’ be equal to π₯ plus three and π£ be equal to nine π₯ plus cosec π₯.
00:10:34.420 --> 00:10:37.540
The derivative of π₯ plus three is simply one.
00:10:37.720 --> 00:10:39.650
But what about dπ£ by dπ₯?
00:10:39.930 --> 00:10:42.760
Well, we know that the derivative of nine π₯ is nine.
00:10:43.100 --> 00:10:47.080
And the derivative of cosec π₯ is negative cosec π₯ cot π₯.
00:10:47.350 --> 00:10:51.440
So dπ£ by dπ₯ is equal to nine minus cosec π₯ cot π₯.
00:10:51.630 --> 00:10:54.600
Letβs substitute what we have into the formula for the product rule.
00:10:54.950 --> 00:11:03.910
We see that dπ¦ by dπ₯ is equal to π₯ plus three times nine minus cosec π₯ cot π₯ plus nine π₯ plus cosec π₯ times one.
00:11:04.380 --> 00:11:08.080
We distribute our parentheses and then collect like terms.
00:11:08.080 --> 00:11:16.190
And we see that dπ¦ by dπ₯ is 18π₯ minus π₯ plus three times cosec π₯ cot π₯ plus cosec π₯ plus 27.
00:11:18.450 --> 00:11:24.550
If π¦ is equal to negative nine tan eight π₯ sec eight π₯, find dπ¦ by dπ₯.
00:11:24.900 --> 00:11:29.240
Here, we have a function which is itself the product of two differentiable functions.
00:11:29.480 --> 00:11:31.240
So weβre going to use the products rule.
00:11:31.570 --> 00:11:40.480
This says that the derivative of the product of two differentiable functions π’ and π£ is π’ times dπ£ by dπ₯ plus π£ times dπ’ by dπ₯.
00:11:40.700 --> 00:11:46.620
So weβll let π’ be equal to negative nine tan eight π₯ and π£ be equal to sec eight π₯.
00:11:46.880 --> 00:11:52.230
We then quote the general result of the derivative of tan ππ₯ is π sec squared ππ₯.
00:11:52.410 --> 00:12:02.360
And this means the derivative of negative nine tan eight π₯ is negative nine times eight sec squared eight π₯, which is negative 72 sec squared eight π₯.
00:12:02.680 --> 00:12:06.230
We also quote the general result for the derivative of sec ππ₯.
00:12:06.320 --> 00:12:13.120
Itβs π sec ππ₯ times tan ππ₯, which means that dπ£ by dπ₯ is eight sec eight π₯ times tan eight π₯.
00:12:13.360 --> 00:12:17.150
We can now substitute everything we know into the formula for the products rule.
00:12:17.470 --> 00:12:29.920
Itβs π’ times dπ£ by dπ₯ plus π£ times dπ’ by dπ₯, which is negative 72 tan squared eight π₯ sec eight π₯ minus 72 sec cubed eight π₯.
00:12:31.860 --> 00:12:40.500
Weβll consider one more demonstration of the use of the results of the derivatives of reciprocal trigonometric functions.
00:12:41.300 --> 00:12:48.680
Given that π¦ is equal to seven cot five π₯ plus three cosec six π₯ to the negative one, find dπ¦ by dπ₯.
00:12:48.970 --> 00:12:51.100
In this example, we have a reciprocal function.
00:12:51.380 --> 00:12:54.480
We could write this as a fraction and apply the quotient rule.
00:12:54.760 --> 00:12:56.640
Alternatively, we could use the chain rule.
00:12:56.930 --> 00:12:58.880
Letβs look at how we might use the chain rule.
00:12:59.190 --> 00:13:08.180
This says that if π¦ is a function in π’ and π’ itself is a function in π₯, then the derivative of π¦ with respect to π₯ is dπ¦ by dπ’ times dπ’ by dπ₯.
00:13:08.430 --> 00:13:13.430
We will let π’ be equal to seven cot of five π₯ plus three cosec six π₯.
00:13:13.650 --> 00:13:16.590
This means that π¦ is equal to π’ to the negative one.
00:13:17.030 --> 00:13:20.370
The derivative of π¦ with respect to π’ is fairly straightforward.
00:13:20.400 --> 00:13:23.410
Itβs negative one times π’ to the negative two.
00:13:23.860 --> 00:13:34.420
Then we quote the derivative for cot ππ₯ as being negative π cosec squared ππ₯ and the derivative of cosec ππ₯ as being negative π cosec ππ₯ cot ππ₯.
00:13:34.620 --> 00:13:44.290
So we see dπ’ by dπ₯ is equal to negative 35 cosec squared five π₯ minus 18 cosec six π₯ cot six π₯.
00:13:44.420 --> 00:13:47.960
The derivative of π¦ with respect to π₯ is the product of these two.
00:13:48.310 --> 00:13:53.540
And we recall that we can write negative π’ to the negative two as one over negative π’ squared.
00:13:53.740 --> 00:14:01.410
We then divide through by negative one and replace π’ with seven cot five π₯ plus three cosec six π₯.
00:14:01.970 --> 00:14:16.510
And weβve obtained dπ¦ by dπ₯ to be equal to 35 cosec squared five π₯ plus 18 cosec six π₯ cot six π₯ over seven cot five π₯ plus three cosec six π₯ all squared.
00:14:17.820 --> 00:14:27.540
In this video, weβve seen that we can use the quotient rule to find the derivatives of the reciprocal trigonometric functions, cot of π₯, sec of π₯, and cosec of π₯.
00:14:27.910 --> 00:14:33.870
We saw that the derivative of the cot of ππ₯ plus π is negative π cosec squared ππ₯ plus π.
00:14:34.310 --> 00:14:40.490
We learned that the derivative of sec of ππ₯ plus π is π sec of ππ₯ plus π times tan of ππ₯ plus π.
00:14:40.810 --> 00:14:47.680
And the derivative of cosec of ππ₯ plus π is negative π cosec ππ₯ plus π times cot of ππ₯ plus π.
00:14:48.190 --> 00:14:56.240
And we saw how we can use these standard results in conjunction with the rules of differentiation to find the derivatives of a large number of functions.